The role of acute toxicity data for South African freshwater macroinvertebrates in the derivation of water quality guidelines for salinity - Browne, Samantha (Rhodes University, Faculty of Science, Department of Environmental Science, 2005)
Water resources are under ever-increasing pressure to meet the demands of various water users both nationally and internationally. The process of anthropogenically-induced salinisation serves to exacerbate this pressure by limiting the quantity and quality of water available for future use. Water quality guidelines provide the numerical goals which water resource managers can use to adequately manage and protect aquatic ecosystems. Various methods which have been developed and used internationally to derive such guidelines are discussed. Acute toxicity tests were conducted using two inorganic salts, NaCl and Na₂SO₄. Field collected, indigenous, freshwater macroinvertebrates were used as tests organisms. Data generated from these tests contributed to the expansion of the currently limited toxicological database of response data for indigenous organisms and the suitability of using such organisms for future testing was discussed. Salt sensitivities of indigenous freshwater invertebrates were compared those of species sourced from an international toxicological database and were found to have similar ranges of tolerances to NaCl and Na₂SO₄. Species sensitivity distributions (SSDs), a method of data extrapolation, were derived using different types of toxicological data, and hence different guideline values or protective concentrations were derived. These concentrations were equated to boundary values for South Africa's ecological Reserve categories, which are used to describe degrees of health for aquatic ecosystems. Provisional results suggest that using only acute toxicity data in guideline derivation provides ecosystem protection that is under-protective. Chronic toxicity data, which include endpoints other than mortality, provide the most realistic environmental protection but lack data confidence due to small sample sizes (acute tests are more readily conducted than chronic tests). The potential contribution of sub-chronic data to guideline derivation is highlighted as these data are more readily extrapolated to chronic endpoints than acute data and sub-chronic tests are not as complex and demanding to conduct as chronic tests.
Keywords: Water-supply -- South Africa; Water quality management -- South Africa; Aquatic ecology -- South Africa; Ecosystem management -- South Africa; Freshwater invertebrates -- South Africa -- Ecology; Water -- Toxicology -- South Africa; Water quality biological assessment